Adhesive Bonding of Aircraft Composite Structures Non-destructive Testing and Quality Assurance Concepts - Leite Cavalcanti, Welchy; Brune, Kai; Noeske, Michael; Tserpes, Konstantinos; Ostachowicz, Wiesław M.; Schlag, Mareike (Springer International Publishing : Imprint: Springer, 2021)
This book is open access under a CC BY 4.0 license. It presents the results of the ComBoNDT European project, which aimed at the development of more secure, time- and cost-saving extended non-destructive inspection tools for carbon fiber reinforced plastics, adhered surfaces and bonded joints. The book reports the optimal use of composite materials to allow weight savings, reduction in fuel consumptions, savings during production and higher cost efficiency for ground operations. .